Are you sara? ebook A novel. - Lalli, S.C (2022)
INTERNATIONAL BESTSELLER Called One of the Best Books of the Year by NPR "Dynamic women with complicated lives take center stage in this twisty mystery about a rideshare mix-up which results in murder. Lalli is a fresh voice in the thriller genre and a writer to watch!" —Wendy Walker, internationally bestselling author of Don't Look For Me Two women named Sara each get into a rideshare. . . but only one makes it home alive. Which Sara was the real target? Law student Saraswati "Sara" Bhaduri holds down two jobs in order to make her way through school, but it's still a struggle. She's had to do things to pay the bills that most people wouldn't expect from "a nice Indian girl." It seems like an ordinary busy Tuesday night at the local dive bar until her boss demands Sara deal with a drunk girl in the bathroom. The two become fast friends. Why? Because they both have the same name. And despite their different circumstances, the two connect. When they both order rideshares home, they tumble in the back of the cars and head out into the night. But when Sara awakes in her rideshare, she finds she's on the wrong side of town—the rich side—and she realizes: she and Sarah took the wrong cars home. With no money, Sara walks back to her apartment on the shady side of town only to discover police lights flashing and a body crumpled on her doorstep: Sarah. Was Sarah Ellis or Sara Bhaduri the target? And why would anyone want either of them dead? In this smart, twisty novel about ambition, wealth, and dangerous longing, the layers are peeled back on two young women desperate to break out of the expectations placed on them, with devastating results.